The Impact of Social Media in Promoting Cultural Communication Between Peoples (The International Journal of Educational Sciences and Arts, 2025)
Research Title: The Impact of Social Media in Promoting Cultural Communication Between Peoples. The research aims to identify the impact of social media (Twitter) on cultural communication between peoples and explore the factors that enhance or hinder this role. The importance of this study lies in light of the rapid digital transformations that have made social media platforms effective tools for transferring knowledge and exchanging values ​​and cultures between individuals from around the world. The research focuses on analyzing the nature of the role played by Twitter in this context, while exploring the factors that contribute to enhancing or hindering cultural communication, such as the nature of the content circulating, platform policies, user behavior, and the extent of societies' openness to interacting with other cultures. The study adopted a descriptive and analytical approach, through a review of relevant literature and an analysis of several cultural accounts and discussions on Twitter. The results concluded that Twitter can be an effective tool in spreading cultural awareness and rapprochement between peoples, provided that it provides positive and interactive content supported by digital policies that promote tolerance and understanding. The study recommends the development of digital communication strategies that promote the conscious use of social media in the service of global cultural dialogue.
Keywords: Social Media; Twitter; Cultural communication; Interaction between Peoples